STUDENTS' PERCEPTION ON READING STRATEGIES FOR IMPROVING READING COMPREHENSION - Prihandini, Yulita Estin (2014)
The study analyzed the students' perception on reading strategies for improving reading comprehension. Qualitative and quantitative approaches were employed in this study. The obtained data were analyzed by using Pearson Product Moment Correlation in finding whether there is any correlation between students' reading strategies and reading comprehension test. Data collected from interview were analyzed by using descriptive qualitative analysis method. Related to students' perception on reading strategies for improving reading comprehension, it was found that students have positive attitude toward reading strategies since they were aware that reading strategies can help them in reading comprehension. The perception can be influenced by self-esteem, which in turn is affected by interaction with teachers, classmates, and family, eventually impacting their motivation for reading.But in facts, there were some students who often applied reading strategies have lower score in reading test compared to students who frequently applied the strategies. The result shows that the correlation coefficient (robt) equals 0.457. The correlation between students' reading strategies and reading comprehension test has positive direction, although the correlation is very low. The fact shows that although high and low achievers used similar reading strategies but the result is different in their reading scores. It depends on how effective students use their strategies. Keywords:reading, reading strategies, students' strategies and students' perception.